Job Satisfaction Variables: A Grounded Theory Approach. (7th June 2016) - Izvercian, Monica; Potra, Sabina; Ivascu, Larisa
Abstract: In a competitive environment organizations are turning towards an important internal wealth, their employees. Because satisfied employees are considered to perform and stay loyal, the present paper examines the viewpoints in the literature regarding job satisfaction and delimits the need to address the variables which influence and explain the high and low satisfaction for the specific Romanian labor market. Additionally, the authors aim to discuss the variable differences between the public and the private sector. The Grounded Theory methodology was chosen due to its ability to extract theory from data. The qualitative research focused on 14 in-depth semi-structured interviews with professionals from the Romanian public and private sector. After a thorough analysis, six main job satisfaction variables emerged with sub-elements. All 36 determinants were included in a new honeycomb model of job satisfaction variables which offers a strategic perspective for human resource management strategies.